Application of metakaolin and cement in the stabilisation of expansive soil: an experimental study - Demelew, Muluager Bewket; Kacprzak, Grzegorz; Kassa, Semachew Molla (Archives of Civil Engineering, 2026)
Expansive soils have the inherent property of swelling when they have adsorbed water and shrink when dried. This property of expansive soil causes damage to structures constructed on it. To minimise the impact of the expansive soil, it is necessary to improve existing soil before commencing infrastructural construction activity. Samples were collected from Debre Tabor City from three test pits and tested for identification and characterisation. The soil was improved with cement content of 3%, 5%, 8%, and 10% by the dry weight of the soil. The results show that the optimum cement content was obtained at 10% and that half of the optimum cement content was replaced by metakaolin with 5%, 8%, 11%, and 14%, respectively, 7%, 20%, 23%, 26%, and 29%. The optimum combined additive decreases the plasticity index from 64.76% to 27.5%, free swell index from 134% to 45%, maximum dry density from 1.33 g/cm3 to 1.36 g/cm3, California bearing ratio value from 1.28% to 5.15% at 5% cement and 17% metakaolin.